EVALUATION OF SPBE SERVICE MATURITY LEVEL IN CENTRAL MALUKU DISTRICT GOVERNMENT USING SPBE 2020 FRAMEWORK - arifin La Adu; Rudy Hartanto; Silmi Fauziati (JIKO (Jurnal Informatika dan Komputer), 2023)
Information and Communication Technology (ICT) utilization in the implementation of government processes is a priority that the government continues to develop. To make it happen, the government, through Presidential Decree No. 95 of 2018 concerning the implementation of an electronic-based government system (SPBE), every government agency must implement SPBE in its services and evaluate the implementation of SPBE periodically. With this urgency, the government issued Panrb Regulation No. 59 of 2020 concerning guidelines for assessing the maturity level of SPBE to correct deficiencies in the previous Panrb Regulation No. 5 of 2018 because there were several mandates of Presidential Regulation No. 95 of 2018 that had not been accommodated in it. One of the domains that received changes is the SPBE Service domain. In the SPBE service domain, there are updates to the assessment questionnaire and the addition of indicators that were originally 11 service indicators to 16 maturity-level service indicators. The purpose of this study is to determine the maturity level of SPBE services using the SPBE 2020 framework through the assessment of aspects of electronic-based Government Administration Services and the value of electronic-based Public Service aspects in Central Maluku regency. The Data in this study were obtained through interviews, observation, and validation of supporting evidence. The results of this study indicate the value of the SPBE Service Domain index of 2.36. The result of this value is used as an assessment of the maturity level of SPBE services in the Central Maluku regency government. From the acquisition of the index value, the maturity level of SPBE services in the Central Maluku regency government is included in the “average” category. To improve the indicators of low-value SPBE services, the Central Maluku regency government needs to implement the improvement recommendations that have been given.